PEMANFAATAN MEDIA SOSIAL DALAM MENINGKATKAN PENJUALAN BISNIS KERIPIK PISANG DI DESA KALIDADI, KALIREJO LAMPUNG TENGAH - Anggalia Wibasuri; Isnandar Agus; Anggawidia Wibaselppa; Suci Mutiara (Jurnal Publika Pengabdian Masyarakat, 2022)
Era of disruption, industry must be more creative and innovative to survive. Not a few entrepreneurs who lost money and were forced to close their businesses because they were not ready to face competition in the era of disruption. The importance of innovation in marketing strategies to solve product marketing problems through promotions to market goods requires a lot of labor or human resources so that their products can be introduced to the public, sales are limited because the business range is not wide, if you want to expand your business you must have a more business place many. For this reason, the purpose of this Community Service activity which is carried out independently with outreach and counseling methods is to provide information and additional knowledge needed by Banana Chips SMEs in Kalidadi Village, Kalirejo, Central Lampung by utilizing social media